Assessment of heavy metal contamination in sediment at Sukinda ultramafic complex using HAADF-STEM analysis. (October 2017) - Equeenuddin, Sk. Md.; Pattnaik, Binaya Kumar
Abstract: The Sukinda ultramafic complex in Odisha has the largest chromite reserve in India. Sediment derived from ultramafic rocks has been enriched with various metals. Further, mining activities enhance the influx of metals into sediment by dumping mine overburden and tailings in the open area. Metal concentration in sediment is found in order of CrTotal (Cr) > Mn > Ni > Co > Zn > Cu with average concentration 26, 778 mg/kg, 3098 mg/kg, 1813 mg/kg, 184 mg/kg, 116 mg/kg and 44 mg/kg respectively. Concentration of Cr(VI) varies from 5.25 to 26.47 mg/L with an average of 12.27 mg/L. Based on various pollution indices, it is confirmed that the area is severely contaminated. Nano-scale goethite, kaolinite, clinochlore and chromite have been identified and have high concentration of Cr, Co and Ni. Goethite has shown maximum metal retention potential as deciphered by high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM). The HAADF-STEM mapping and principal component analysis indicate that Cr and Co mostly derived from chromite whereas Ni and Zn are derived from serpentine. Later, these metals co-precipitate and/or adsorbed onto the goethite and clay minerals. Fractionation study of metals confirms that Cu is the most mobile element followed by Zn. However, at low pH condition Ni is mobilized and likely to be bioavailable. Though Cr mostly occurs in residual fraction but as its concentration is very high, a small proportion of exchangeable fraction contributes significantly in terms of its bioavailability. Thus bioavailable Cr can pose severe threat to the environment in the Sukinda ultramafic complex. Highlights: Detailed sediment geochemistry has been performed in the Sukinda ultramafic complex. Sediment has very high concentration of Cr, Cr(VI), Ni, Co and Mn. Nano-scale goethite, kaolinite, clinochlore and chromite have been identified. Chromite is the source of Cr and Co while Ni is derived from serpentine. Bioavailbale Ni and Cr can pose serious environmental threat in the area.